The model of quality assessment of automatically adjusted responsive web pages and applications - Plechawska-Wojcik, M. (Искусственный интеллект, 2013)
The paper presents a model, which can be applied to Graphical User Interface testing. The model is dedicated especially to web pages and web applications created using Responsive web design. The procedure is based on expert method and cognitive walkthrough. The paper outlines contain the description of responsive web design, used methodology, GUI evaluation process and the application description.